184k views
3 votes
Help me pleaseeeeeeeeeeeeee!!!!

Help me pleaseeeeeeeeeeeeee!!!!-example-1
User Planplan
by
4.9k points

2 Answers

3 votes

Answer:

okay with what

Explanation:

User Lawrence Kok
by
5.0k points
4 votes

Answer:

8.3 seconds

Explanation:

-16t² + 24t + 900 = h

Let h = 0.

-16t² + 24t + 900 = 0

4t² - 6t - 225 = 0


t = (-b \pm √(b^2 - 4ac))/(2a)


t = (6 \pm √((-6)^2 - 4(4)(-225)))/(2(4))


t = (6 \pm √(36 + 3600))/(8)


t = (6 \pm √(3636))/(8)


t = 8.2874


t = -6.787

Answer: 8.3 seconds

User Ankit Patial
by
4.3k points